ECONOMICAL OPTIMIZATION OF CONDUCTOR SELECTION IN PLANNING RADIAL DISTRIBUTION NETWORKS - Ab Ghani, Mohd Ruddin (1999)
A new computer algorithm and program is presented for selection of optimal conductor type and size for each feeder segment. An acceptable voltage profile is maintained along the entire feeder of the network while obtaining an objective of minimizing the total cost, which consists of capital investment, and cost of feeder losses, etc. Node numbering scheme and node connection sequence selection have been proposed to determine the node current and voltage drop for each individual node and termination end of each feeder branches and power loss of each segment of the feeder. If the conductor size available fail to satisfy the user defined constraints the designer can rerun the program after making the relevant changes to the inventory database. The proposed method has been successfully applied in the solution of an example of distribution network that is presented.